Assessment of the Baltic States on regulation of plastic packaging recycling - Karaļuna, Marija Elīza (Riga Graduate School of Law, 2019)
Today plastic is being produced in large quantities, generating large amounts of plastic waste that is not sufficiently recycled, as a result plastic accumulation in the environment have led to serious plastic pollution that affects water quality, wildlife and human health. The EU, which is the focus of this thesis, is trying to find solutions in order to prevent plastic pollution in the environment through regulations. The purpose of the thesis is to examine recycling performance in the Baltic States in order to assess to what extent Baltic States have implemented existing EU directives regarding packaging waste and waste management, and to determine the preparedness of the Baltic States for the new EU initiative to prevent plastic pollution by adopting EU Strategy for Plastics in a Circular Economy.
Keywords: Environmental law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Baltic states